2013
DOI: 10.1016/j.bbamem.2013.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol modulates water permeation through Escherichia coli aquaglyceroporin GlpF

Abstract: Among aquaglyceroporins that transport both water and glycerol across the cell membrane, Escherichia coli glycerol uptake facilitator (GlpF) is the most thoroughly studied. However, one question remains: Does glycerol modulate water permeation? This study answers this fundamental question by determining the three-dimensional potential of mean force of glycerol along the permeation path through GlpF's conducting pore. There is a deep well near the Asn-Pro-Ala (NPA) motifs (6.5 kcal/mol below the bulk level) and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 49 publications
2
51
0
Order By: Relevance
“…[23] This experimentally measured value validates GlpF’s free-energy profile computed in Ref. [41] that resembles PfAQP’s profile discussed above.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…[23] This experimentally measured value validates GlpF’s free-energy profile computed in Ref. [41] that resembles PfAQP’s profile discussed above.…”
Section: Resultssupporting
confidence: 83%
“…The current literature does not have all the data to fully validate this theoretical prediction but a careful analysis of the existent in vitro experiments was done in Ref. [41] showing that the presence of glycerol suppresses water conduction through aquaglyceroporin. For example, Song et al[11] examined water permeability of PfAQP expressed in protoplasts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…46. The starting positions of the two Au 144 S 60 cores’ COMs were set at locations (x,y,z) = (0,0,±2.5) nm.…”
Section: Methodsmentioning
confidence: 99%
“…Hu et al (2014) demonstrated that exogenous glycerol inhibited primary root growth. In bacteria, it has been postulated that glycerol modulates water permeation in the micromolar range, whereas at millimolar concentrations, E. coli GlpF is glycerol saturated, occluding the conducting pore (Chen, 2013). In yeast, S. cerevisiae Fps1 plays critical roles in osmoregulation by modulating the accumulation of glycerol (reviewed in Ahmadpour et al, 2014).…”
Section: Nip4;1 and Nip4;2 Transport Water And Glycerol In Oocytesmentioning
confidence: 99%